DOUBTS WITH ACUTE CORONARY SYNDROME PATIENTS FOLLOWING THE PROSPECTIVE ANALYSIS - Bilen, Mehmet Nail; Ozbay, Yilmaz; Yavuzkir, Mustafa; Balin, Mehmet; Dagli, Necati; Karaca, Ilgin (Elsevier Ireland Ltd, 2010)
[Abstract Not Available]